Caracterização acustica de telhas sanduíche ou compostas e seus componentes: estudo de caso - Tamiosso, Larissa Seminoti (2017)
Users are increasingly complaining about the acoustic comfort of buildings, especially in large urban centers. A NBR 15575: 2013 - Housing Buildings - Performance brought changes in the construction sector, which had to be concerned with the characterization of products and construction systems. Another important norm for the comfort of the users was the NBR 16373: 2015 - Tiles and panels acoustic - Performance Requirements, which aims to qualify the coverings, which are little studied, especially from the perspective of acoustics. The present dissertation aims to characterize the experimental acoustic performance of two types of aluzinco sandwich tiles and their constituent elements, evaluating their performance in relation to the Brazilian standard. The first type of tile analyzed consisted of: tile + EPS + flat beveled sheet. The second composite tile consisted of: tile + EPS. In addition, the alumina tile was tested individually and, subsequently, only the EPS. NBR 16373: 2015 was used for conducting the absorption and loss of sound transmission tests. The experimental procedure to determine the Sound Absorption Coefficient (α) used the reverberant chamber method, standardized by the International Standard ASTM C423: 2013. From the analysis of the data, the results showed a higher absorption when the EPS was apparent in the composition of the tile, which is the format used in large industrial pavilions, when analyzed from the interior to the exterior. Regarding the sound insulation, the samples were tested according to ISO 10140: 2010, in reverberant chamber. The best performance was achieved with the tile typology + EPS + flat bevelled sheet that reached a Rw = 26 dB, performance classified by NBR 16373: 2015 in scale 3 and was the best classified sample. Regarding the sound insulation, the samples were tested according to ISO 10140: 2010, in reverberant chamber. In this way, new tests with other insulators such as rock wool and glass wool are proposed, as well as to verify the performance of the tiles in relation to impact noise.